Interdomain communication suppressing high intrinsic ATPase activity of Sse1 is essential for its co‐disaggregase activity with Ssa1. (11th September 2019) - Kumar, Vignesh; Peter, Joshua Jebakumar; Sagar, Amin; Ray, Arjun; Jha, Mainak Pratim; Rebeaud, Mathieu E.; Tiwari, Satyam; Goloubinoff, Pierre; Ashish, Fnu; Mapa, Koyeli
Abstract : In eukaryotes, Hsp110s are unambiguous cognates of the Hsp70 chaperones, in primary sequence, domain organization, and structure. Hsp110s function as nucleotide exchange factors (NEFs) for the Hsp70s although their apparent loss of Hsp70‐like chaperone activity, nature of interdomain communication, and breadth of domain functions are still puzzling. Here, by combining single‐molecule FRET, small angle X‐ray scattering measurements (SAXS), and MD simulation, we show that yeast Hsp110, Sse1 lacks canonical Hsp70‐like interdomain allostery. However, the protein exhibits unique noncanonical conformational changes within its domains. Sse1 maintains an open‐lid substrate‐binding domain (SBD) in close contact with its nucleotide‐binding domain (NBD), irrespective of its ATP hydrolysis status. To further appreciate such ATP‐hydrolysis‐independent exhaustive interaction between two domains of Hsp110s, NBD‐SBD chimera was constructed between Hsp110 (Sse1) and Hsp70 (Ssa1). In Sse1/Ssa1 chimera, we observed undocking of two domains leading to complete loss of NEF activity of Sse1. Interestingly, chimeric proteins exhibited significantly enhanced ATPase rate of Sse1‐NBD compared to wild‐type protein, implying that intrinsic ATPase activity of the protein remains mostly repressed. Apart from repressing the high ATPase activity of its NBD, interactions between two domains confer thermal stability to Sse1 and play critical role in the (co)chaperoning function of Sse1 in Ssa1‐mediated disaggregation activity. Altogether, Sse1 exhibits a unique interdomain interaction, which is essential for its NEF activity, suppression of high intrinsic ATPase activity, co‐chaperoning activity in disaggregase machinery, and stability of the protein. Abstract : Hsp110s are structural cognates of Hsp70 chaperones. Despite obvious similarity in 3D structures, Hsp110s are functionally different from Hsp70s. We show that yeast Hsp110, Sse1 lacks Hsp70‐like ATP‐hydrolysis‐dependent domain allostery and exhibits a domain‐docked state irrespective of its ATP hydrolysis status. Interdomain contacts of Sse1 are essential for its exchange factor function, suppression of high intrinsic ATPase activity, co‐disaggregase activity with Ssa1, and overall stability of the protein.